2023
DOI: 10.3390/ijms24108699
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dopamine D3 Receptors, Dysbindin, and Their Functional Interaction in the Expression of Key Genes for Neuroplasticity and Neuroinflammation in the Mouse Brain

Abstract: Cognitive impairment in schizophrenia remains a clinically and pharmacologically unsolved challenge. Clinical and preclinical studies have revealed that the concomitant reduction in dysbindin (DYS) and dopamine receptor D3 functionality improves cognitive functions. However, the molecular machinery underlying this epistatic interaction has not yet been fully elucidated. The glutamate NMDA receptors and the neurotrophin BDNF, with their established role in promoting neuroplasticity, may be involved in the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Subsequent treatment with N-acetylcysteine (NAC) or omega-3 polyunsaturated fatty acids (PUFAs), both anti-in ammatory agents, resulted in a reduction in the severity of schizophrenia in offspring. Another study by V. Rivi et al [29] examined the expression levels of NF-κB-related pro-in ammatory factors IL-6, TNF-a, and IL-1β in patients with schizophrenia and found a close association between their levels of onset of schizophrenia. Furthermore, in an upper interaction between dopamine receptor D3 and schizophrenia-associated proteins (DYS), it was found that lower dopamine receptor D3 function led to higher pro-in ammatory cytokines in double-mutant mice compared to single heterozygous mice (DYS +/− and D3 +/−) with down-regulated GRIN1 and GRIN2A mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent treatment with N-acetylcysteine (NAC) or omega-3 polyunsaturated fatty acids (PUFAs), both anti-in ammatory agents, resulted in a reduction in the severity of schizophrenia in offspring. Another study by V. Rivi et al [29] examined the expression levels of NF-κB-related pro-in ammatory factors IL-6, TNF-a, and IL-1β in patients with schizophrenia and found a close association between their levels of onset of schizophrenia. Furthermore, in an upper interaction between dopamine receptor D3 and schizophrenia-associated proteins (DYS), it was found that lower dopamine receptor D3 function led to higher pro-in ammatory cytokines in double-mutant mice compared to single heterozygous mice (DYS +/− and D3 +/−) with down-regulated GRIN1 and GRIN2A mRNA levels.…”
Section: Discussionmentioning
confidence: 99%